Zonal and Regional Jupiter Brightness Trends from the Hubble Outer Planet Atmospheres Legacy Program - Amy A. Simon; Michael H. Wong (The Planetary Science Journal)
The Hubble Outer Planet Atmospheres Legacy program began in 2014 and has observed Jupiter yearly from 2015 to 2024. Using high spatial resolution imaging from the Hubble Wide Field Camera 3, brightness trends were investigated focusing on the unique UV capability and absolute calibration consistency of the Hubble Space Telescope. From these data, a 4–5 yr period is observed at 24° north, particularly in the blue (F395N) and methane gas absorption (FQ889N) filters. Additionally, several wavelengths show a potential seasonal periodicity, especially at the equator, but more years of data are needed to confirm this trend over multiple Jupiter years. Variability in Oval BA and the Great Red Spot brightness is not cyclical, but these two anticyclonic features show changes on a yearly timescale.